A CONVERSATIONAL IMPLICATURE ANALYSIS IN “THE WENDY WILLIAMS SHOW” SELECTED EPISODES - Laksmy Ady Kusumoriny; Setiana Sri Wahyuni Sitepu; Nahoras Bona Simarmata (Universitas Pamulang, 2022)
Implicature is one of pragmatics branches which has an interesting subject to learn. It is also known by conversational implicature. This study identifies two types of conversational implicature and the implicit meanings in The Wendy Williams Show. The data were identified and analyzed from the guest’s and the host’s utterances in the Wendy Williams Show. The collected data were identified and analyzed by the writers using Grice (1975) theory. This study used qualitative method as a research method. The writers took 23 episodes, and in each episode, there were 1 up to 4 utterances contained implicit meanings. As a result of the study, it was found that there are 29 particularized conversational implicature and 21 generalized conversational implicature from 50 utterances were taken from The Wendy Williams Show. From the analysis it can be concluded that every utterance has different context in delivering messages which contains the implied meaning.